Historicising the Metapolitefsi: A Review of the Three Publications of the Themelio Metapolitefsi Series - Markatos, Kimon (Historein, 2018)
Review of three publications: Manos Avgeridis, Efi Gazi and Kostis Kornetis (eds.), Μεταπολίτευση: Η Ελλάδα στο μεταίχμιο δύο αιώνων [Metapolitefsi: Greece at the crossroads of two centuries]. Athens: Themelio, 2015. 448 pp. Vangelis Karamanolakis, Ilias Nikolakopoulos and Tasos Sakellaropoulos (eds.), Η μεταπολίτευση ’74-’75: Στιγμές μιας μετάβασης [The metapolitefsi, 1974–75: moments of a transition]. Athens: Themelio, 2016. 248 pp. Leonidas Kallivretakis, Δικτατορία και μεταπολίτευση [Dictatorship and metapolitefsi]. Athens: Themelio, 2017. 280 pp.